São Paulo: avanços e recuos, após quase uma década da política de mudança do clima - Jane Zilda dos Santos Ramires; Neli Aparecida de Mello-Théry (Confins)
In 2009, at the forefront of the state and federal governments, São Paulo enacted the climate change law, an important and significant step to the largest megacities on the planet that accumulates all the socio-environmental problems of an aggressive and disorderly urban expansion. As the city expands the rates of water and atmospheric pollution increase, its green areas and springs decrease and areas of risk are forged to accommodate the lower income population, who do not support the price to live in legal city. Issues related to traffic, mobility and energy generation further highlight the challenges to be faced by the local governments. To make the cities and the human settlements, inclusive, safe, resilient and sustainable is what advocate The New Urban Agenda of the United Nations (UN) approved at the Third United Nations Conference on Housing and Sustainable Development (Habitat III) in 2016. This article intends to analyze local public actions, starting in 2009, considering the context of climate change and UN objectives, in particular regarding mitigation and adaptation to climate change, favoring the use and occupation of the soil in the city of Sao Paulo.